Application of Red Ginger Decoction (Zingiber Officinale Var. Rubrum) to lower blood pressure In Hypertension Patients - Syahrun, Syahrun; Atika Amalia Sholikhah; Metungku, Fanny; Iskandar Muda (Fakultas Kedokteran, Universitas Mulawarman, 2024)
Background: Hypertension is a dangerous condition, especially at the age of 40, and there is an increase in the number of sufferers. One of the non-pharmacological treatments is red ginger decoction (Zingiber Officinale Var. Rubrum). Purpose: find out the decrease in blood pressure in the administration of red ginger decoction. Methods: Case study research design, conducted by observing blood pressure in 3 respondents which was carried out for 7 days. Results : Average decrease between 5 – 10 mmHg in Systole and 10 – 15 mmHg in Diastole pressure. Conclusion: Red ginger decoction has been proven to lower blood pressure in hypertensive patients, it can be used as a complementary therapy. However, during the administration of the stew, the condition of blood pressure must be monitored before giving the decoction. Keywords: Hypertension; Red ginger; Zingiber Officinale Var. Rubrum